The Commercialization of Migration Control - Andrijasevic, Rutvica (Citizenship and its Others, 2015)
In her chapter entitled ‘The Convergence of the Criminal and the Foreigner in the Production of Citizenship’, Melanie Griffiths discusses the emergence in the United Kingdom of a figure of so-called ‘foreign national offender’ (FNO) or simply, the ‘Foreign Criminal’. This figure merges the figure of the ‘criminal’ with the ‘foreigner’, and is commonly deployed to denote a ‘young, black or Muslim man (or, more recently, as also a white Eastern European man)’ (Griffiths, this volume, p. 75). The Foreign Criminal is a legal and moral construction and stands in relation to the citizen as its significant Other. The chapter illustrates the social and political implication of this normative category on three individuals by exemplifying the punitive measures that the three men were subjected to by the police and the Home Office as well as the adjustments that the men made to cope with the situation. They all endured heightened police control, imprisonment for minor crimes, prolonged immigration detention and threat of deportation. These are political, social and symbolic processes that produce a particular type of a marginalized political subject marked by its gender (that is male) and its race (that is black). The logic of the Foreign Criminal is, Griffiths argues, less about reducing criminal risk or removing those without the right to remain in the country than of maintaining the social order and defining the Community of Value.